High-speed solar-blind UV photodetectors using high-Al content Al0.64Ga0.36N/Al0.34Ga0.66N multiple quantum wells. (21st December 2016) - Muhtadi, Sakib; Hwang, Seong Mo; Coleman, Antwon L.; Lunev, Alexander; Asif, Fatima; Chava, V. S. N.; Chandrashekhar, M. V. S.; Khan, Asif
Abstract: We demonstrate high-external quantum efficiency (∼50%) solar-blind AlGaN p–n junction photodetectors with high-Al content multiple quantum wells (MQWs). A peak responsivity of 0.1 A/W at 250 nm, which falls >10 3 by 280 nm, indicates that the optical absorption is dominated by the MQW structures. At a reverse bias of 0.5 V, the dark current is <0.1 pA. The readout RC-limited time response is measured as 0.4 µs, and an achievable detector RC-limited time response of 2 ns is estimated. The devices do not show internal gain, which accounts for their high speed.